2003
DOI: 10.1007/s11661-003-0147-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of solidification time and heat treatment on the fatigue properties of a cast 319 aluminum alloy

Abstract: the form of acicular needles, blocky plates, or a refined fibrous structure (Figure 1). Also present are intermetallic phases and porosity, both of which can be deleterious to the fatigue resistance of cast 319 Al alloys. These features can act as stress raisers for crack nucleation or as low-energy paths for crack propagation. In general, increasing the solidification rate tends to reduce the average size of these features as well as to promote a finer distribution of gas and microshrinkage porosity.The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 18 publications
3
77
0
Order By: Relevance
“…1 (right) the fatigue strength S aD50% , is plotted against the mean pore size d equ . The data, taken from literature [1][2][3][4] as well as from own fatigue tests, include AlSi7-alloys with varying Mg-and Cu-content as well as different heat treatment conditions (T6, T7, F). All data lie within the same scatter band and can be described using a Kitagawa-model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 (right) the fatigue strength S aD50% , is plotted against the mean pore size d equ . The data, taken from literature [1][2][3][4] as well as from own fatigue tests, include AlSi7-alloys with varying Mg-and Cu-content as well as different heat treatment conditions (T6, T7, F). All data lie within the same scatter band and can be described using a Kitagawa-model.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding threshold value K th is in the range of 2.0 to 2.8 MPa √ m. For slip band induced fracture origin it was found that fatigue strength can be estimated based on the materials yield strength, since the yield strength correlates with the resistance toward dislocation movement necessary for the formation of fatigue slip bands. This result was based on data from literature [1,3,5] of different Sr-refined AlSi7-alloys with varying Mg-and Cu-content in T6 and T7 heat treatment conditions in addition to own fatigue results using specimens from HIPed components.…”
Section: Resultsmentioning
confidence: 99%
“…The third source of porosity develops from the natural volume contraction which occurs when a liquid solidifies; this is often referred to as microshrinkage porosity. 40 The presence of porosity is crucial in that it lowers the soundness of a casting and thereby its mechanical properties.…”
Section: -Porositymentioning
confidence: 99%
“…Savelli et al 61 studied two AlSiMgO.3 alloys with different porosity contents with regard to fatigue properties. It was observed that quantitative parameters characterizing size or shape of internal pores could be measured on three dimensional reconstructed images and correlated to the fatigue properties.…”
Section: Effect Of Porosity On Fatigue Properties Of Al-si Casting Almentioning
confidence: 99%